TINGKAT KECEMASAN DAN STRES PADA KELUARGA PASIEN DENGAN TALASEMIA: LITERATURE REVIEW - Sarah Florencia Manurung; Darwin Karim; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2021)
Thalassemia is an inherited blood disorder, that affects the body’s ability to produce hemoglobin and red blood cells. In order to increase the life expectancy, the patients are dependent on blood transfusions. This situation requires serious attention and dedication from family members to take care of the patients. On the other hand, not all family members are able to accept and adapt easily. The family feels guilty, angry, stressed, and anxious. The purpose of this study is to describe the level of anxiety and stress in the families of patients with thalassemia. This study is based on the literature review method, which used sn m/kome tools to find related articles such as google scholar and semantic scholar. The English keywords are level of family anxiety AND level of family stress AND thalassemia while Indonesian keywords are tingkat kecemasan keluarga DAN tingkat stres keluarga DAN talasemia in the period of 2016-2020. From the 1.462 articles that were screened, 5 articles were analyzed. According to the literature review from 5 articles, the majority of respondents were female (88,46%) with the majority of the ages ranging from 25-49 years (54,52%). The result of the study on the level of anxiety in the families of the patients with thalassemia from the 3 articles that were analyzed, the majority of respondents had moderate anxiety level. Meanwhile the result of the study on stress levels in the families of patients with thalassemia from the 2 analyzed had moderate stress level. It is highly recommended for health professionals who are treating patients with thalassemia to acces psychological issues that could emerge in family members. Keywords: Level of family anxiety, level of family stress, thalassemia